Distribution of episodes of kidney diseases admitted at the University Hospital Center "Mother Teresa" in Tirana, Albania, during the period 2010-2023 - Marsida Duli; Qamil Dika; Elizana Petrela; Genc Burazeri (PAGEPress Publications, 2024)
Our aim was to describe the distribution of kidney diseases among hospitalized patients in Tirana, the capital of Albania, during the period 2010-2023. A case-series study was conducted including all episodes admitted with kidney diseases at the University Hospital Center "Mother Teresa" in Tirana during the period 2010-2023 (overall: 15,763 episodes; 46% females; overall mean age: 54.0±17.3 years). We found that ≈56% of the kidney disease episodes were 35-65 years old, followed by >65-year-old individuals (≈28%). Most of the kidney disease episodes (about 43%) hospitalized were from the Tirana region, followed by districts pertinent to South Albania (23%). Older patients (>65 years) were more prevalent among males compared to females (301% vs 25%, respectively; p<0.001). Patients from the Tirana region were more prevalent among females compared to males (45% vs 42%, respectively, p<0.001). This study provides evidence on the distribution of the episodes of kidney diseases admitted at University Hospital Center "Mother Teresa" in Tirana, the largest region in Albania, a country in the Western Balkans that is undergoing deep reforms in all sectors, including also the health sector.